Closed pinning for paediatric supracondylar fractures: does timing really matter? - Surapaneni, Suresh Babu; Kopuri, Ravi Kiran; Tummala, Venkata Suresh Babu (International Journal of Research in Orthopaedics, 2017)
Background: Management guidelines and comparative studies are not yet clear for those patients who present early and late with widely displaced supracondyle humerus fracture in children. Methods: A total of 74 children were included in this study, 30 patients presenting early within 24 hours as group 1, and 44 patients who presented late i.e. after 24 hours and within a week as group 2 underwent closed reduction and pinning. Results: In group one 24 had excellent, 6 had good results, according to modified Flynn’s criteria. One patient developed ulnar nerve palsy which was iatrogenic, and improved completely after wire removal. Another was brachial artery injury which was explored and recovered completely. In group 2 the average delay in presentation was 57.56 hours; mean time to surgery after presentation was 9.83 hours. Sixteen patients (36.36%) had neurologic complications at presentation to the emergency room of which three had median nerve palsy (6.81%) whereas seven (15.90%) had isolated anterior interosseous nerve palsy and six (13.6%) had radial nerve palsy all patients showed total neurological recovery at 12 weeks. Six patients (13.63%) had vascular compromise at initial presentation of which five patients had feeble radial pulse and one had absent radial pulse, but capillary filling was adequate in all. The pulse was restored within 24 hours in all patients following reduction. There were 37 excellent, 6 good and 1fair results. Conclusions: Our results support, closed reduction and Percutaneous pin fixation as an effective treatment option for grossly displaced supracondylar fractures presenting early and late but requires good and careful judgment and also technique.